Pemanfaatan Agregat Sungai To Puang Kabupaten Tana Toraja Sebagai Bahan Campuran Beton - Misel Boro Allo; Herman Parung; Junus Mara (Program Studi Teknik Sipil UKI Paulus-Makassar, 2021)
Entering the New Normal 2021 era due to the Covid-19 pandemic, all industries began to develop again, especially infrastructure development projects. Everyone is competing to take the initiative to create quality and efficient concrete by using the materials around it. This research focuses on the utilization of the aggregate of the To Puang River, Tana Toraja Regency as a concrete mix stacking material, to determine the value of compressive strength, split tensile strength value, flexural strength value, and elastic modulus value. The mix design of this study used the SNI 7656:2012 method. In this study, the planned quality target was f'c = 28 MPa with a water-cement factor (fas) of 0.44. The results of this study indicate that the average compressive strength is 30.290 MPa, the average split tensile strength is 2.902 MPa, the average flexural strength is 3.376 MPa, and the modulus of elasticity is 20820.747 MPa.